Glycosidases in porcine follicular fluid and their effect on zona pellucida-AWN 1 spermadhesin interaction - Dráb, Tomáš; Ren, Štěpán; Maňásková-Postlerová, Pavla; Tichá, Marie; Jonáková, Věra; Liberda, Jiří (Theriogenology, 2017)
Oligosaccharide moieties on the surface of the oocyte belong to the key molecules that direct the course of fertilization and are subjected to changes during oocyte maturation in the follicle. In our study, we focused on the activities of five glycosidases in the fluids from porcine secondary and preovulatory follicles (α-l-fucosidase, α-d-galactosidase, β-d-galactosidase, β-D-N-acetylhexosaminidase, and α-d-mannosidase). All of them were detected active at neutral and acidic pH. However, changes in their activities associated with follicle development were observed only in the case of α-d-mannosidase, which was increased (P < 0.001), and β-d-galactosidase, which was decreased (P < 0.001) at neutral pH, and of α-d-galactosidase and β-N-acetylhexosaminidase, which were decreased (P < 0.0001) at the acidic pH. The comparison of glycosidases from follicular fluid and from blood plasma using red native electrophoresis revealed that most of the glycosidases are present in more than one isoenzyme form; some of them were detected mainly in the follicular fluid. Finally, we tested the effect of glycosidases on the interaction between zona pellucida and AWN 1 spermadhesin (putative sperm receptor of zona pellucida) and demonstrated that the effect of both β-d-galactosidase and to a lesser degree α-d-mannosidase led to a decrease in this interaction. We can hypothesize that these two glycosidases modulate the amount of zona pellucida oligosaccharide moieties and/or their structures for an optimal sperm binding in pigs.
Keywords: glykosidhydrolasy; oocyty; Biotinylation; prasata; proteiny semenné plazmy; Animals; zvířata; Seminal Plasma Proteins; Glycoside Hydrolases; čipová analýza proteinů; Protein Array Analysis; biotinylace; Swine; Zona Pellucida; Follicular Fluid; folikulární tekutina; ženské pohlaví; Female; zona pellucida; Oocytes